Binding Authority of a Previous Award, Trial Period Denied (Relations industrielles / Industrial Relations, 1961)
SummaryThe arbitrator of the same agreement has no authority to reverse or alter it in a subsequent case. An employee, in order to fulfil the normal requirements of his job, has no right to a training period.